"The map, the navigator, and the explorer": evaluating the content and quality of CBT case conceptualization and the role of self-practice/self-reflection as a training intervention : a thesis presented in partial fulfillment of the requirements of the Doctor of Philosophy in Psychology at Massey University, Albany, New Zealand - Haarhoff, Beverly Ann (Massey University, 2008)
Cognitive Behaviour Therapy (CBT) leads the way as an evidenced based psychotherapy, and the evaluation of CBT training programs is increasingly seen as important if this position is to be maintained. In this dissertation, CBT case conceptualization, as a core psychotherapeutic competency, acquired in training, is evaluated. Case conceptualization, integrates precipitating, predisposing, maintaining, and protective factors, functioning as an explanatory and prescriptive roadmap for therapy. Gaining self-knowledge through exposure to some form of personal therapy is cited as important in gaining psychotherapeutic competency. Self-practice/ self-reflection, show promise as a form of personal therapy compatible with the principles of CBT. This study evaluates the content and quality of CBT case conceptualizations produced by a sample of 26 participants who have completed the Massey University Post Graduate Diploma, using three case conceptualization rating scales. In addition, the impact of a self-practice/self-reflection manualised training intervention designed to improve the quality of case conceptualization in trainee cognitive behaviour therapists, is explored using thematic analysis. The evaluation of the CBT conceptualizations showed predisposing factors and psychological mechanisms as receiving the most attention from participants. However, the majority of participants failed to pay attention to socio-cultural, biological, protective factors and factors pertaining to the therapeutic relationship. The majority of the participants were able to produce a 'good enough' CBT case conceptualization, however the ‘problem list’ was not well developed, and the conceptually relevant aspects of the therapeutic relationship and protective factors were given less attention. The effect of a self-practice/self-reflection training intervention on the quality of CBT case conceptualizations produced by the intervention group (n = 16) drawn from the main participant sample, was qualitatively evaluated using thematic analysis. Theoretical understanding of the model, self awareness, empathy, conceptualization of the therapeutic relationship, adaptation of clinical interventions, and clinical practice were all subjectively perceived by participants to have increased as a result of the intervention. An inferential analysis compared the performance of the intervention group (n=16) that of a comparison group (n=10), made up of the remainder of the larger sample described in the context of the first question. The comparison group had not been exposed to the manualised intervention. The comparison was both within, and between the two groups. The quality of the intervention group showed an improvement on one of the rating scales, indicating a possible link between the training intervention and case conceptualization competency, however, the improvement was not replicated by the other two rating scales. The findings are discussed in the context of improving CBT training with regard to case conceptualization.
Keywords: Cognitive Behaviour Therapy; Psychotherapy; Fields of Research::380000 Behavioural and Cognitive Sciences::380100 Psychology::380107 Health, clinical and counselling psychology